Hubungan faktor demografi guru dengan kepuasan kerja di sekolah menengah dalam bahagian Miri, Sarawak - Tang, Siu Ting (2012)
The purpose of this study is to study job satisfaction among teachers in Miri Division. The research is also aim to find the correlation between demography factor and jobs satisfaction of teachers in Miri Division, Sarawak. 200 teachers from four schools had been the respondents for this research. 'JDI' by Smith et al (1975) and adapted by Mohd Majid (1990) for local usage is used to process the data. Programme SPSS Window Versi 14 is used to analyze the data descriptively and inferentiately to obtain teachers' information such as frequency, mean, and median. Pearson 'r' correlation is used to find the relation between jobs satisfaction and age, gender, ethnic, groups, experience and location of the school. The findings of the research from these five demography factors, that is, age, gender, ethnic group, experience and location of school which is tested for the relation with job satisfaction, only gender, ethnic group and experience has significant with job satisfaction. Characteristics like age and location of school do not influence job satisfaction among teachers in secondary school in Miri Division, Sarawak. Even though characteristics such as gender, ethic group and experience are significant with job satisfaction but the correlation is at very low level. Furthermore, this research can serve as a suggestions for organization research guideline for further research. At the end of this study, there are several recommendations are presented to increase the level of job satisfaction among teachers in Miri, Sarawak